New media and green behaviour campaign through corporate social responsibility collaboration - Sri Hilmi Pujihartati; Ismi Dwi Astuti Nurhaeni; Drajat Tri Kartono; Argyo Demartoto (Penerbit Universiti Kebangsaan Malaysia, 2023)
This research delves into the role of new media in promoting green behaviour campaigns as part of community development programs supported by corporate social responsibility (CSR) initiatives. In particular, the program under investigation involves a collaboration between the community and the CSR division of Indaco Warna Dunia Company. Employing the sociology of communication analysis, this study aims to reveal the importance of new media platforms in disseminating environmental messages that resonate with the younger generation. In the current age of rapid communication and information exchange, new media has the potential to overcome the challenges posed by traditional channels and engage young people, who play a crucial role in driving social and environmental change. By leveraging new media, environmental messages can be effectively communicated to the youth, fostering a generation that is conscious of sustainable practices and environmental issues. To investigate the impact of new media on promoting green behaviour, this research utilised a single holistic case study methodology. The findings of this study indicate that social media, as a form of new media, can serve as a contemporary and effective means of disseminating environmental education. By utilising these platforms, green behaviour campaigns can reach a wider audience, inspire young people to adopt eco-friendly habits, and ultimately contribute to the development of environmentally-conscious communities through strategic CSR collaborations.